1996
DOI: 10.1007/bf00369213
|View full text |Cite
|
Sign up to set email alerts
|

Visualization of crystal-matrix structure. In situ demineralization of mineralized turkey leg tendon and bone

Abstract: A technique to correlate the ultrastructural distribution of mineral with its organic material in identical sections of mineralized turkey leg tendon (MTLT) and human bone was developed. Osmium or ethanol fixed tissues were processed for transmission electron microscopy (TEM). The mineralized tissues were photographed at high, intermediate, and low magnifications, making note of section features such as fibril geometry, colloidal gold distribution, or section artifacts for subsequent specimen realignment after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(44 citation statements)
references
References 13 publications
2
42
0
Order By: Relevance
“…which is consistent with the interface viscosity of η i = 1.83 × 10 12 GPa s m −1 as given in [22], and an interface radius of 50 nm, consistent with electron microscopic images [30]. In order to study interaction among two interface families exhibiting different interface sizes and viscosities, the corresponding product a 2 η i,2 , referring to the second interface family, is considered to be a multiple of the amount given in (108),…”
Section: Study Of Interface Interaction In a Relaxation Testsupporting
confidence: 87%
See 2 more Smart Citations
“…which is consistent with the interface viscosity of η i = 1.83 × 10 12 GPa s m −1 as given in [22], and an interface radius of 50 nm, consistent with electron microscopic images [30]. In order to study interaction among two interface families exhibiting different interface sizes and viscosities, the corresponding product a 2 η i,2 , referring to the second interface family, is considered to be a multiple of the amount given in (108),…”
Section: Study Of Interface Interaction In a Relaxation Testsupporting
confidence: 87%
“…This expectation is supported by the theoretical derivation of Ponte Castañeda and Willis [28] that the Mori-Tanaka scheme actually considers spatial distributions of inhomogeneities following the same ellipsoidal shape as the inhomogeneities themselves. For material systems targeted at by our approach, including calcium silicate hydrates in concrete [29], extrafibrillar spaces in bone [30], or montmorillonite interlayers in clay [31], these spatial distributions appear as natural and appropriate. The remaining two state equations establish relations between dislocation vectors of the two interface families,…”
Section: State Equations For Uniform Strain Boundary Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Such micromechanical models predict, on the basis of mechanical properties of bone elementary constituents (hydroxyapatite, collagen, water), the (poro-)elasticity tensors at the different hierarchical levels of the material, from tissue-specific composition data, such as porosities and mineral/collagen content. There-the explicit consideration of the extrafibrillar mineral crystals whose existence was evidenced earlier [Lees et al, 1984a, 1994, Prostak and Lees, 1996, Pidaparti et al, 1996, Benezra Rosen et al, 2002, and further confirmed by the kinetics of recent demineralization experiments [Balooch et al, 2008]. In this sense, the challenge of micromechanics-supported, consistently upscaled microstructure-property relationships for poroelasticity in bone has been met quite reasonably.…”
Section: Introductionmentioning
confidence: 83%
“…Many previous TEM studies using microtome-cut sections of bone concluded that much of the mineral in bone resided in the gap zone between collinear triple helices of collagen (e.g., [27][28][29][30][31]). While there is a wide consensus that a large part of the mineral of bone must also lie outside the fibrils ( [32][33][34][35][36][37][38][39][40][41][42][43][44][45]), the detailed structure of this extrabrillar component was poorly known before the use of ion milling for preparation of TEM samples.…”
Section: Three-dimensional Organization Of Bone At Nanoscale Tem Imagmentioning
confidence: 99%